The Bangun Tidur Board (Sleeping Shapes Board): An Alternative Learning Media for Solving GCF and LCM Story Problems in Elementary Schools - Atiulloh, Siti; Wiryanto, Wiryanto; Ekawati , Rooselyna (Journal of Innovation and Research in Primary Education, 2025)
This study aims to develop and evaluate the effectiveness of the Bangun Tidur Board (Sleeping Shapes Board) as an alternative learning media to improve elementary students’ self-efficacy and problem-solving ability in greatest common factor (GCF) and least common multiple (LCM) story problems. The research employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model as the instructional design framework, involving 21 fifth-grade students from SDN Sidokepong 1, Sidoarjo, in the academic year 2024/2025 under the Merdeka Curriculum. Data were collected through tests, self-efficacy questionnaires, and documentation, while statistical analyses included normality, homogeneity, paired t-test, N-gain, and effect size. The findings revealed significant improvement in students’ problem-solving performance and self-efficacy, with moderate to high N-gain values and a strong effect size. These results demonstrate that the Sleeping Shapes Board provides a concrete and engaging medium for representing mathematical concepts, enabling students to visualize relationships in FPB and KPK more effectively. Moreover, the integration of real-life story contexts fostered students’ confidence and motivation in tackling mathematics problems. The study highlights that systematically developed media grounded in contextual learning not only enhances cognitive understanding but also nurtures affective aspects of learning. This research contributes to mathematics education by offering an innovative, practical, and classroom-tested medium that aligns with the principles of the Merdeka Curriculum and supports the dual goals of conceptual mastery and self-efficacy in elementary mathematics.